IDENTIFICATION OF JOGGING TRACK POTENTIAL BASED ON 4A IN BAHA TOURISM VILLAGE, MENGWI SUB-DISTRICT - Suparmi Ni Ketut; I Wayan Runa; Agus Kurniawan (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2024)
Baha Village is one of eleven other villages in Badung Regency designated as a Tourism Village by the Badung regional government. Baha Village has a tracking path as one of its tourist attractions. Located in a rice field area of 273 hectares with a length of 6 km tracking lane, it allows tourists to visit rice fields, travel by bicycle, exercise, enjoy natural beauty and feel the beautiful rural atmosphere. With its potential, it allows the development of jogging track tourism in Baha Tourism Village in a sustainable manner. The purpose of this research is to identify the potential of the jogging track based on 4A (Attracktion, Accessibility, Amenity, Ancilliary), The analysis method that can be used is the SWOT matrix, this matrix can clearly describe how the external opportunities and threats faced are aligned with its strengths and weaknesses. This matrix can generate four sets of alternative strategies as follows: 1) The SO (Strenght - Opportunity) strategy concluded that the location of Baha Tourism Village is considered strategic with the existence of tracking paths, rice field views, and the Balai Subak museum as the main potential. The support of the Badung Regency government in financing development is a significant advantage. This conclusion shows that Baha Tourism Village can take advantage of its internal strengths to optimize existing external opportunities. 2) The WO (Weaknes-Opportunity) strategy concludes that despite limitations in supporting facilities and electrical infrastructure, Baha Tourism Village can maximize its potential by utilizing financial support from the Badung Regency government. Utilizing external financing can help overcome internal weaknesses and create conditions that are more conducive to the development of jogging track tourism. 3) Strategy ST (Strenght - Threats) then obtained the conclusion Although there is competition with other tourist villages that have similar concepts, Baha Tourism Village can develop by maximizing its unique potential. The addition of artificial tourism such as mushroom restaurants, fishing parks, and the tradition of metekap by farmers can create its own attraction, differentiate Baha Tourism Village from competitors and overcome potential external threats.4) WT Strategy (Weakness - Threats) It is concluded that facing challenges from similar tourist village concepts, Baha Tourism Village needs to create new icons to attract tourists. This approach involves developing uniqueness such as flower gardens as photo spots, metekap attractions from farmers, and mushroom restaurants. Thus, Baha Tourism Village can overcome internal limitations and potential external threats by presenting something new and interesting.